1970
DOI: 10.1063/1.1672713
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Quasilocalized Excitons in Molecular Crystals

Abstract: Articles you may be interested inEffects of impurity scattering and transport topology on exciton migration and trapping: An experimental study of quasionedimensional molecular crystals A model is presented for electron-phonon coupling in molecular crystals ~nd its effect on transport?f excitons and charge carriers in aromatic hydrocarbon crystals. The model differs from the usual ones In that the coupling is taken quadratic instead of linear in the vibrational coordinates. It is shown that this coupling domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Munn and Siebrand [30] have shown that a one-dimensional crystal with a single impurity has three types of normal modes: (1) symmetric, (2) antisymmetric, and (3) localized (around the impurity site). If the number of sites is n, then there are (n -1)/2 symmetric modes, (n -1)/2 antisymmetric modes, and one localized mode ( Table I).…”
Section: Vibrational Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Munn and Siebrand [30] have shown that a one-dimensional crystal with a single impurity has three types of normal modes: (1) symmetric, (2) antisymmetric, and (3) localized (around the impurity site). If the number of sites is n, then there are (n -1)/2 symmetric modes, (n -1)/2 antisymmetric modes, and one localized mode ( Table I).…”
Section: Vibrational Characteristicsmentioning
confidence: 99%
“…Three parameters, namely J (electronic coupling between adjacent molecules), wl (vibrational coupling between adjacent molecules), and w2 (exciton-phonon coupling) are important in the consideration of excition diffusion [30]. For quasilocalized or slow excitons in a molecular crystal J is very much smaller than w , (the slow exciton limit).…”
Section: Hamiltonianmentioning
confidence: 99%
See 1 more Smart Citation
“…While very simple, this model is not trivial and already allows studying a variety of phenomena that include spectral lineshapes [9], electron transfer [10,11], electron-phonon interaction in quantum dots [12,13], and quantum control [1,[14][15][16][17][18][19][20][21][22]. The independent boson model fundamentally deals with the consequences of electronic excitations that induce a spatial shift in the vibrational modes [23][24][25], and in some materials like aromatic hydrocarbons, a frequency change [26][27][28][29][30][31][32]. Instead of using the physically relevant phonons that depend on the occupied level of the electronic system, i.e.…”
mentioning
confidence: 99%
“…r( k). tim es the group velocity of the wavepacket : (3) l(k) is thus equivalent to a mean-free path and r(k) corresponds to a correlation time for the wave vector state kor linear combination of k states at an energy E;(k) associated with the zeroth order state. From a dynamical point of view the important feature of coherent migration is that excitons can propagate in the crystal at a variety of velocities and a variety of distances depending upon the k states populated.…”
Section: Introductionmentioning
confidence: 99%